2022
DOI: 10.3390/su142214952
|View full text |Cite
|
Sign up to set email alerts
|

Strength, Durability, and Microstructure of Foamed Concrete Prepared Using Special Soil and Slag

Abstract: Foamed concrete (FC) is a lightweight building material widely used in thermal insulation walls, backfill, and other fields. Generally, foamed concrete is prepared using cement, which consumes a lot energy and resources. In this study, three kinds of special soil (SS) and slag powder (SP) were used to prepare foamed concrete. The content of SS was 25%, and the content of SP was 35%, 45%, and 55%. The mechanical properties, durability properties, and microstructure of special soil-slag foamed concrete (SSFC) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…There are other approaches to reducing emissions related to the fabrication of building construction materials, such as foamed concrete (FC) and lightweight concrete. FC can be produced with soil or slag powder and is suitable for the thermal insulation of walls or for backfill [15]. Recent studies have also shown that potentially problematic wastes, such as polystyrene and cement kiln dust, can be mixed to create lightweight cementitious bricks as an eco-friendly alternative to traditional cement bricks [16].…”
Section: Research Backgroundmentioning
confidence: 99%
“…There are other approaches to reducing emissions related to the fabrication of building construction materials, such as foamed concrete (FC) and lightweight concrete. FC can be produced with soil or slag powder and is suitable for the thermal insulation of walls or for backfill [15]. Recent studies have also shown that potentially problematic wastes, such as polystyrene and cement kiln dust, can be mixed to create lightweight cementitious bricks as an eco-friendly alternative to traditional cement bricks [16].…”
Section: Research Backgroundmentioning
confidence: 99%
“…Instead of fly ash, other types of waste are used in foam concrete, for example, various types of slag. In the study [28], compositions of foam concrete with slag were developed. It has been established that with the introduction of slag from 25% to 55%, with increasing its dosage, the characteristics of the composite deteriorate.…”
Section: Introductionmentioning
confidence: 99%